A comparison of attack angle dependence of exchange channel of reaction H + HS (v = 0, 1; j = 0) on 3A″ and 3A′ surfaces. Issue 24 (1st August 2013) - Li, Wenliang; Zhai, Hongsheng; Feng, Yan; Zhao, JuanJuan
<x xml:space="preserve">Abstract</x> In this theoretical work, we report quasiclassical dynamics predictions for the attack angle‐dependence exchange processes for the H + HS (v = 0, 1; j = 0) reaction by using the new triplet 3A″ and 3A′ potential energy surfaces, respectively. The calculated quasiclassical reaction probabilities of exchange reaction channel of reaction H(D)′ + H(D)S for J = 0, 10, 20, 30, 40 are in good agreement with quantum wave packet results over the collision energy range from 0.1 to 2.0 eV on 3A″ surfaces. The attack angle dependence reaction probability of the title reactions at J = 0 are calculated, respectively, on the two surfaces. The reaction probability was found to be strongly dependent on the attack angle. It may be ascribe to the significant difference of the effective potential barrier height in the two reactions. Besides, the reaction probabilities of exchange reaction channel of reaction H(D)′ + H(D)S for J = 0, 10, 20, 30, 40 are also predicted on 3A′ surfaces. © 2013 Wiley Periodicals, Inc.